Аналіз магнітодинамічного дефектоскопа залізничних рейок та шляхи його модернізації - Трохим, Г.Р.; Нічога, В.О.; Дуб, П.Б. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
An overview of the system structure of high-speed rail flaw magnetic inspection is presented. The structural changes for the multicomponent diagnostics are proposed.